Electrodialysis membrane desalination with diagonal membrane spacers: a review - Al-Amshawee, Sajjad Khudhur Abbas; Mohd Yusri, Mohd Yunus (Springer, 2023)
Electrodialysis desalination uses ion exchange membranes, membrane spacers, and conductors to remove salt from water. Membrane spacers, made of polymeric strands, reduce concentration polarization. These spacers have properties such as porosity and filament shape that affect their performance. One important property is the spacer-bulk attack angle. This study systematically reviews the characteristics of a 45° attack angle of spacers and its effects on concentration polarization and fluid dynamics. Membrane spacers in a channel create distinct flow fields and concentration profiles. When set at a 45° attack angle, spacers provide greater turbulence and mass-heat transfer than traditional spacers. This is because both the transverse and longitudinal filaments become diagonal in relation to the bulk flow direction. A lower attack angle (<45°) results in a lower pressure drop coupled with a decline in wakes and stream disruption because when the filaments are more parallel to the primary fluid direction, the poorer their affect. This research concludes that membrane spacers with a 45° spacer-bulk attack angle function optimally compared to other angles.